2022
DOI: 10.2754/avb202291010107
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative and qualitative properties of giblets from conventional, organic, and wild ducks

Abstract: The aim of the study was to evaluate selected properties of giblets (liver, heart, and gizzard) from conventional (C), organic (O), and wild (W) ducks. A total of 24 giblets (24 of each organ) were analysed in each bird group. Production properties, colour indicators, haem pigment content and chemical composition were compared. The heaviest organ with the highest yield was the liver in C and W ducks and the gizzard in O ducks (P < 0.05). The liver and gizzard of W and O ducks were darker (P < 0.05) compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 27 publications
(36 reference statements)
1
0
0
Order By: Relevance
“…The results (Table 3) show that the percentage of male local duck offal to live weight is 12.34 ± 1.00%. These results were almost the same as the observations from [36] on the weight of duck offal aged 7 months that were kept organically, which was 154.83 g. The results of previous research showed that ducks supplemented with probiotics in their feed and slaughtered at 6 weeks of age had an 8.30% lower percentage of offal than the results of this study [37]. The weight of the offal of female Peking ducks was 168.8 g, and of male Peking ducks was 129.3 g at the rejected age (27 months) [38].…”
Section: Offal Percentagesupporting
confidence: 91%
“…The results (Table 3) show that the percentage of male local duck offal to live weight is 12.34 ± 1.00%. These results were almost the same as the observations from [36] on the weight of duck offal aged 7 months that were kept organically, which was 154.83 g. The results of previous research showed that ducks supplemented with probiotics in their feed and slaughtered at 6 weeks of age had an 8.30% lower percentage of offal than the results of this study [37]. The weight of the offal of female Peking ducks was 168.8 g, and of male Peking ducks was 129.3 g at the rejected age (27 months) [38].…”
Section: Offal Percentagesupporting
confidence: 91%